The Ventral Premammillary Nucleus Links Metabolic Cues and Reproduction - Donato, Jose; Elias, Carol F. (Frontiers in Endocrinology, 2011)
The amount of body fat and the energy balance are important factors that influence the timing of puberty and the normal reproductive function. Leptin is a key hormone that conveys to the central nervous system information about the individual energy reserve and modulates the hypothalamus-pituitary-gonad axis. Recent findings suggest that the ventral premammillary nucleus (PMV) mediates the effects of leptin as a permissive factor for the onset of puberty and the coordinated secretion of luteinizing hormone during conditions of negative energy balance. Thus, in this review we will summarize the existing literature about the potential role played by PMV neurons in the regulation of the hypothalamus-pituitary-gonad axis.